Efeitos de uma intervenção baseada no treinamento de habilidades da terapia comportamental dialética em indivíduos com obesidade - Cancian, Ana Carolina Maciel (2016)
Over the past 30 years, the prevalence of obesity in the world has doubled, and according to national surveys, about 18% of Brazilians are obese. Obesity is associated with risks to physical and psychological health and a great share of prevention and modification of this multifactorial condition relies on behavior changes. However, some psychological aspects may be barriers to successful treatments, especially when eating is associated with regulation of aversive emotional states. The Dialectical Behavior Therapy (DBT) is an approach that conceptualize problem behaviors as effective attempts to regulate emotions in the short term, but not effective in the long-term. Therefore, it is a central goal in DBT that individuals learn a new repertoire of skills that help to deal with emotions. Section 1 of this study analyzes the effects of a 10 session intervention based on DBT Skills Training on emotion regulation, psychiatric symptoms and dysfunctional and adaptive eating behaviors in obese adults who were randomly assigned to intervention group or to a waiting list comparison condition. This study had measures at pre and posttest, and was quasi experimental. Inclusion criteria were (a) BMI equal to or over 30, (b) adults aged 18 to 59 and (c) at least 8 years of formal study. Participants were excluded if they presented (a) psychotic symptoms, (b) active suicidal ideation or attempted suicide over the last year, (c) the use disorders substances and (d) that had already received any treatment with DBT components. The scales used in the pretest and posttest were Difficulties in Emotion Regulation Scale (DERS), Binge Eating Scale (BES), Emotional Eating Scale (EES), Intuitive Eating Scale (IES-2), Mindful Eating Questionnaire (MEQ) and Depression, Anxiety and Stress Scale (DASS-21). The sample consisted of 31 obese subjects divided into intervention group (n = 14) and waiting list (n = 17). Based on the large effects sizes, the results show that the intervention based on DBT skills training might be effective in reducing the severity of binge eating, improving depressive symptoms and increasing adaptive eating behaviors such as intuitive eating, that is, eating more connected with physiological signals of hunger and satiety. However, the study lacks statistical power to support strong conclusions. These results are therefore preliminary and require replications with larger samples. Section 2 aimed to analyze the semantic equivalence of the DERS for Brazilian Portuguese. For that, it was utilized a five-step adaptation process: (1) translation; (2) back translation; (3) correction and semantic adaptation with the author of the original instrument; (4) content validation by expert judges (n = 10) and; (5) assessment by the general population through a numeric verbal scale (n = 28). The results show that the final version had satisfactory semantic equivalence, with good comprehensibility by expert judges and general population and final approval of the author of the original instrument.